THE MAIN RESULTS OF THE STUDY OF THE PROCESSES OF DEODORIZATION OF VEGETABLE OILS USING WOODEN NOZZLES (Journal of Pharmaceutical Negative Results, 2022)
The article presents for the first time the prospect of using floating movable wooden nozzles in the processing of vegetable oil during the final distillation of vegetable oils in the layer. In the deodorization chamber, extraction oil is supplied from the upper part of the apparatus, and sharp water vapor is supplied from the lower part of the apparatus, as a result of which there is a continuous movement of nozzles in the layer. It is proved that movable float wooden nozzles serve to increase the contact surface between the liquid and vapor phase. Also studied the hydrodynamics of the deodorization process in the "liquid-vapor-floating nozzle" system with the participation of floating wooden nozzles, the dependence of the distribution of wooden nozzles of different sizes on the device height, heat and duration of the mass exchange process.